Simultaneous stable isotope analysis of methane and nitrous oxide on ice core samples - Sapart, Célia; Van Der Veen, C.; Vigano, I.; Brass, M.; van de Wal, Roderik S W; Bock, Michael; Fischer, H.; Sowers, T.; Buizert, C.; Sperlich, P.; Blunier, T.; Behrens, M.; et al. (2011)
info:eu-repo/semantics/published